(3oZQQ GdMce hoOQQ Gdcdes - (3CHhGdaJM fGUM GdOjf YHO GdhGMO Hf eMeO Hf YHO GdhGMO GdJejej GdBeOjs; (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s ((3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3hHYO aEf GdPj MOGfj Ydi JNUjUg ahGFO gPG GdcJGH s
(3BNQgG (B:s
(3jbHM HGdQLd Cf jbUQ Yedg Yf Ydeg, hjYLR aYdg Yf bhdg s
(3ef cdGe GdEeGe Ydj Hf CHj WGdHs
(3GdeJhai (B40 (3g`s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs